(untitled) (Acta Polytechnica CTU Proceedings, 2023)
The aim of this paper is to explore the potential of using inexpensive, commercial electronics such as a smartwatch or chest belt to measure human physiological functions while driving in vehicle simulator, both to improve safety and to use these devices in other experiments to facilitate their conduct and replace more complex laboratory equipment. In the first part of the paper, the signs of stress and cognitive load through physiological functions are researched, then the possibilities of measuring these signs are explored. This is followed by an experiment in which two commonly available devices are compared in terms of accuracy and usefulness for measurement during the experiment.